The autocratic bias: self-censorship of regime support. Issue 4 (19th May 2022) - Tannenberg, Marcus
ABSTRACT: Because of a perceived (and real) risk of repressive action, some survey questions are sensitive in more autocratic countries while less so in more democratic countries. Yet, survey data on potentially sensitive topics are frequently used in comparative research despite concerns about comparability. To examine the comparability of politically sensitive questions, I employ a multilevel analysis with more than 228, 000 respondents in 37 African countries to test for systematic bias when the survey respondents believe (fear) that the government, rather than an independent research institute, has commissioned the survey. The findings indicate that fear of the government induces a substantial and significant bias on questions regarding trust, approval and corruption perceptions in more autocratic countries, but not in more democratic countries. In contrast, innocuous, apolitical questions are not systematically influenced by regime type.